Behind Body Shaming and Colorism: Unveiling the Psychosocial Variations through Body Shapes and Skin Tones - AlSaleh, Aseel; Husain, Waqar; Ghazzawi, Hadeel; Amawi, Adam; Trabelsi, Khaled; Achraf, Ammar; Jahrami, Haitham (Jordan Medical Journal, 2025)
Background: The pursuit of physical attractiveness is universal across cultures and driven by the desire to avoid the detrimental psychosocial consequences of body shaming and colorism. Previous research on body dissatisfaction has focused primarily on anxiety. The aim of the present study was to explore the impact of body shape and skin tone on sociality, emotionality, morality, religiosity, spirituality, personality, psychosocial wellness, and psychosocial illness. Methods: The study was a large-scale nationwide investigation. It involved 14 phases in which a total of 10,127 participants, comprising both men and women, were recruited from Pakistan and Bahrain. Body shape was classified into three categories: muscular/curved, fat/chubby, and slim/thin. Skin tones were categorized as fairly white, pale white, light brown, and dark brown. The data were collected using demographic questionnaires and 21 psychological scales. Results: Muscular men and curvy women exhibited elevated self-esteem, positive emotions, and virtuous traits, albeit with reduced forgiveness levels. Curvy women demonstrated heightened engagement in beautification practices. Fat/chubby individuals showcased heightened religious intelligence but also endorsed traits like infidelity, neuroticism, and anxiety. They displayed deficits in social intelligence and hope. Slim/thin counterparts displayed creativity but also higher levels of charismaphobia. Fairly white individuals showcased self-esteem, creativity, and love capacity, yet reported sexual frustration. Pale white individuals displayed traits like heterosexuality, neuroticism, and charismaphobia, with low courage and teamwork. Light brown individuals exhibited justice, social intelligence, and humor, alongside charismaphobia. Dark brown individuals demonstrated prudence but attitudes toward infidelity, with low transcendence and openness. Conclusion: The study offers new insights into the complex connections of body shapes and skin tones with various psychosocial factors, marking a significant contribution to scientific knowledge. The findings of this study would enable psychologists, psychiatrists, cosmetic-dermatologists, and other relevant practitioners to adequately associate different aspects of psychology with different body shapes and skin tones.